2019
DOI: 10.1016/j.neuron.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Postural Representations of the Hand in the Primate Sensorimotor Cortex

Abstract: Manual dexterity requires proprioceptive feedback about the state of the hand. To date, study of the neural basis of proprioception in the cortex has focused primarily on reaching movements to the exclusion of hand-specific behaviors such as grasping. To fill this gap, we record both timevarying hand kinematics and neural activity evoked in somatosensory and motor cortices as monkeys grasp a variety of objects. We find that neurons in the somatosensory cortex, as well as in the motor cortex, preferentially tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 94 publications
(122 reference statements)
7
45
0
Order By: Relevance
“…Whatever the case may be, the low-dimensional linear dynamics observed in M1 during reaching are not present during grasping, consistent with an emerging view that the cortical circuits that track and control the hand differ from those that track and control the proximal limb ( Goodman et al, 2019 ; Rathelot and Strick, 2009 ).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Whatever the case may be, the low-dimensional linear dynamics observed in M1 during reaching are not present during grasping, consistent with an emerging view that the cortical circuits that track and control the hand differ from those that track and control the proximal limb ( Goodman et al, 2019 ; Rathelot and Strick, 2009 ).…”
Section: Discussionsupporting
confidence: 67%
“…The VICON system tracked the three-dimensional positions of the markers, and time-varying joint angles were computed using inverse kinematics based on a musculoskeletal model of the human arm ( https://simtk.org/projects/ulb_project ) ( Anderson and Pandy, 2001 ; Anderson and Pandy, 1999 ; de Leva, 1996 ; Delp et al, 1990 ; Dempster and Gaughran, 1967 ; Holzbaur et al, 2005 ; Yamaguchi and Zajac, 1989 ) implemented in Opensim ( https://simtk.org/frs/index.php?group_id=91 ) ( Delp et al, 2007 ) with segments scaled to the sizes of those in a monkey limb using Opensim’s built-in scaling function. Task and kinematic recording methods are reported in an earlier publication ( Goodman et al, 2019 ). We used a linear discriminant classifier as detailed in this previous publication to determine whether objects indeed evoked distinct kinematics ( Figure 1—figure supplement 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Position control (i.e., postural control) provided improved performance relative to velocity control ( fig. S6), which is consistent with the natural encoding schemes of the hand (56). The participant received cutaneous sensory feedback from the index contact sensor; proprioceptive sensory feedback was not provided, although endogenous proprioception of residual forearm muscles and efference copy may have been present.…”
Section: Object Discrimination Taskssupporting
confidence: 60%
“…The specificity of the responses we observed in low-level visual cortex may reside on specific retinotopic-like maps in visual cortex for tactile location as recently shown for spatial sound (Norman and Thaler 2019). It has been also shown that the response fields of sensorimotor neurons are distributed over the entire hand (Goodman et al 2019). Taken together with our observations, one could argue that this specific organization is reflected in visual cortex.…”
Section: Discussionsupporting
confidence: 87%